ANALISIS PENGARUH SPACING ANTAR ELEMEN TERHADAP GAIN PADA ANTENA YAGI 5 ELEMEN FREKUENSI 2,4 GHz - Ade Saputra; Hanesman Hanesman; Sukaya Sukaya (Universitas Negeri Padang, 2015)
This research was motivated by a relatively small laptop power receives Wi-Fi signals, so it needs a directional antenna that has a high gain Yagi antenna like. This research is to: demonstrate the effect of spacing between elements to Yagi antenna gain, get the fixed spacing, knowing gain of Yagi antenna being tested and how much spacing between elements effect to gain enhancement statistically. This research use Gain Comparison Method. It is performed by CST Studio Suite simulation and measurements on 3 measurement points (TP), in a free barrier room, prevented plywood, and walled. Minimum and maximum of Spacing is 0,05λ and 0,35λ. The analysis showed: (1) Changes the spacing between elements of Yagi antenna using CST Studio Suite and the design of the AUT antenna proven effect on the gain. Changing the minimum space to maximum increase the gain untill the optimal space, then decreased. (2) The fixed spacing settings by optimal space. Space-1 optimal of simulation is 0,115λ; 0,205λ for space-2; 0,2λ for space-3, and 0,22λ for space-4. Space-1 optimal of Yagi AUT is 0,127λ, space-2 = 0,201λ, space-3 = 0,196λ, and space-4 = 0,22λ. (3) Simulastion result has gain 9,8 dB, Yagi AUT has 9,68 dB, and the commercial Yagi antenna by 14 elements has 11,84 dB. (4) The regression coefficient for space-1 (X1) is -58,534 <distance coefficient of signal source to TP (X2). Space-2 (X1) coefficients = -12,53 < X2 coefficient = -12,543. Space-3 (X1) coefficients = 0,72 > X2 coefficient = -1,289. Space-4 (X1) coefficients = 30,939 > X2 coefficient = -1,332. Keywords : Spacing of Elements, Gain, Yagi Antenna, Gain Comparison Method, CST Studio Suite